ANALISIS HUBUNGAN PEMANFAATAN LABORATORIUM TERHADAP KETERAMPILAN PROSES SAINS (KPS) PESERTA DIDIK - Zafira ,; Yosi Laila Rahmi; Ganda Hijrah Selaras (Jurnal Ilmiah Pena: Sains dan Ilmu Pendidikan, 2022)
Utilization of the laboratory through practical activities is important to carry out in the learning process because it can support students' understanding of the subject matter so that it is hoped that learning outcomes in the form of Science Process Skills will increase. This study was conducted to collect sufficient information on the analysis of the relationship between the use of laboratories and the Science Process Skills of students. The method used in this study is through a literature study that collects several previous studies to answer the relationship between the use of laboratories and the Science Process Skills of students. The results of the study mostly stated that the use of laboratories had a considerable influence on the Science Process Skills of students. Based on the results of this literature study, it can be concluded that there is a positive and significant relationship between the use of laboratories and the science process skills of students.Keywords: Laboratory, Science Process Skills, Literature Study